2018
DOI: 10.2147/cmar.s174095
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of aspartate aminotransferase to platelet ratio index as a noninvasive biomarker in patients with hepatocellular carcinoma: a meta-analysis

Abstract: BackgroundThe aspartate aminotransferase-to-platelet ratio index (APRI) has been correlated with clinical outcome in patients with hepatocellular carcinoma (HCC), but controversial results were obtained with previous studies. This study was aimed to evaluate the prognostic value of the APRI in patients with HCC.Materials and methodsA literature survey was conducted by searching PubMed, Web of Science, Cochrane library, Embase, Wanfang, and National Knowledge Infrastructure for publications released prior to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Another factor relating to liver function is hepatic fibrosis, and the AST-to-platelet ratio index (APRI) is a widely used alternative to liver biopsy to detect liver fibrosis [ 14 ]. We found that an APRI value over 1 was associated with poor OS after RFA, consistent with study results that APRI could serve as a marker for predicting HCC prognosis [ 15 ]. Regarding tumor-related factors, we found that tumor size greater than 3 cm and tumor number greater than 1 were both associated with a poorer prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Another factor relating to liver function is hepatic fibrosis, and the AST-to-platelet ratio index (APRI) is a widely used alternative to liver biopsy to detect liver fibrosis [ 14 ]. We found that an APRI value over 1 was associated with poor OS after RFA, consistent with study results that APRI could serve as a marker for predicting HCC prognosis [ 15 ]. Regarding tumor-related factors, we found that tumor size greater than 3 cm and tumor number greater than 1 were both associated with a poorer prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…As a simple and noninvasive marker, APRI consists of two routinely available biochemical and clinical parameters, aspartate aminotransferase (AST) and platelets (PLT), which can be calculated according to the following formula: (AST/the upper limit of normal value)/PLT (10 9 /L) × 100 [34]. Thus, APRI, as a composite biomarker, is less expensive and widely available [16, 35, 36] and its clinical value can be enhanced due to its stability and reliability [28].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recent studies have illuminated the potential of inexpensive and readily accessible non-invasive biomarkers like albumin (ALB)-to-alkaline phosphatase (ALP) ratio (AAPR), aspartate aminotransferase (AST)-to-alanine aminotransferase (ALT) ratio (AAR), AST-to-platelet ratio index (APRI), and fibrosis-4 index (FIB-4) as valuable prognostic indicators for predicting disease progression and long-term survival in HCC patients. [13][14][15][16][17][18] The nomogram, a straightforward visualization tool, is constructed by integration and quantization of numerous independent risk factors, which can be used to accurately and individually identify high-risk patients and predict prognosis, and its application can enhance the clinical management and prognosis assessment for HCC patients. 19,20 However, the relationship between non-invasive biomarkers and PVTT events remains elusive, and few nomogram models are available for predicting the prognosis of HBV-related HCC patients without PVTT.…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers have shown significant associations with the prognosis of HCC patients. [15][16][17]31,32 AAR is calculated from the serum AST and ALT levels and serves as a sensitive indicator of hepatocellular injury. ALT is predominantly located in the cytoplasm, while AST is found in both the cytoplasm and mitochondria.…”
mentioning
confidence: 99%